Lokakarya Pendidikan Terkait Pemanfaatan Konsep Matematika dalam Kehidupan Sehari-hari di Universitas Qamarul Huda Badaruddin - Ratna Yulis Tyaningsih; Laila Hayati; Dwi Novitasari; Tabita Wahyu Triutami; Nilza Humaira Salsabila (Pendidikan Matematika, FKIP Universitas Mataram, 2022)
Advances in technology and information today are the application of various sciences and the underlying science is mathematics. Mathematics is one of the basic provisions that are important to master in dealing with increasingly complex life problems. Through mastery of mathematics, it makes someone have good logical thinking in solving the problems at hand. In terms of responding to problems that arise, making decisions, and prioritizing appropriately, it is necessary to involve analytical skills and mathematical logic. However, many students do not know the application of mathematics in various disciplines. This community service activity is carried out in the form of an educational workshop with the theme Utilization of Mathematical Concepts in everyday life. The target of this community service activity is students from various study programs at the University of Qamarul Huda Badaruddin (UNIQHBA). Through this activity, it is hoped that it can contribute to the entire UNIQHBA academic community regarding the application of mathematics in various fields, especially culture, economics, and development, providing examples of skills related to mathematics so that they have more insight and are ready to compete in the world of work.